On densities for solutions to stochastic fixed point equations. Issue 3 (21st September 2018) - Leckey, Kevin
Abstract: We consider systems of stochastic fixed point equations that arise in the asymptotic analysis of random recursive structures and algorithms such as Quicksort, large Pólya urn processes, and path lengths of random recursive trees and split trees. The main result states sufficient conditions on the fixed point equations that imply the existence of bounded, smooth, rapidly decreasing Lebesgue densities.